Are there threatened snakes at the end of the rainbow?: Notes on the distribution and morphology of Epicrates cenchria, Rainbow Boa, in the Brazilian Atlantic Forest - Andrade-Junior, Albedi (2020)
We report on new voucher specimens of Epicrates cenchria to the meridional limits of its distribution in the Atlantic Forest. We provide data on the meristic, morphometric and hemipenial morphology features for this southernmost population. We review the recent published record of E. cenhria for the locality of Ipiguá, state of São Paulo, Brazil, and reidentify it specimen herein to as E. crassus. Finally, we comment on the niche models available to E. cenchria and other congeners, suggesting outstanding issues that require additional studies.